Transethosome Technology: Revolutionizing Transdermal Drug Delivery - R.Patil, Sneha; Dharashive, Vishveshwar; Shafi, Sameer; Rudrurkar, Muktai N.; Kazi, Anis J.; Ritthe, Punam V. (Asian Journal of Pharmaceutical Research and Development, 2024)
In recent years, transdermal drug delivery has become increasingly popular as it overcomes issues with oral administration. The main challenge in this method is the complex stratum corneum barrier that prevents the transdermal administration of drugs. However, modern lipid-based nanosystems, particularly transethosomes, can effectively penetrate the dense network of the stratum corneum. Transethosomes are a promising and unique technique for improved transdermal medication administration via the skin, as compared to transferosomes and ethosomes. They are composed of phospholipid, ethanol, water, and edge activators or permeation enhancers. The combination of ethanol and edge activators allows the medication molecules to be delivered into circulation. There are various techniques used in the formulation of transethosomes, including the Cold method, Hot method, Thin film hydration method, and Mechanical dispersion method. Transethosomes have small particle sizes and can easily change the shape of vesicles, allowing them to pass through the layers of skin. The characterization of vesicles includes the size of the particle and surface charge, Transmission Electron microscopy, determination of entrapment efficiency, surface morphology study, interaction study by DSC and FTIR, drug content, and stability of vesicles. The transdermal route using UDV can administer various medication classes, including anti-arthritic, antibacterial, anticancer, antiviral, and analgesic.